2020
DOI: 10.1177/1747021820977038
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-orthographic segmentation of opaque and transparent derived words: New evidence for Spanish

Abstract: Semantic transparency has been extensively analyzed in research on visual word recognition. Under the masked priming paradigm, it has consistently been shown that opaque and transparent words are facilitated relative to form-related controls, but differences in priming between one condition and another have not been conclusively proven. Hence, research has been unable to theoretically elucidate the possible value of semantic transparency in the processing of derived words. This study describes two lexical deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Previous masked priming lexical decision evidence in Spanish employing the classical contrast in which the stem is present both in primes and targets (i.e., employing morphological or pseudomorphological words as primes) has led to similar facilitatory effects in semantically transparent pairs and pseudomorphological pairs (Lázaro et al 2021), supporting the results found in other languages (Beyersmann et al, 2016; Grainger & Beyersmann, 2020; Hasenäcker et al, 2016; Rastle et al, 2004). There is also evidence in Spanish showing that when derivational morphemes are used as masked primes, they facilitate the recognition of semantically transparent and pseudomorphological target words, compared to form-related controls (Lázaro, Illera, & Sainz, 2016).…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…Previous masked priming lexical decision evidence in Spanish employing the classical contrast in which the stem is present both in primes and targets (i.e., employing morphological or pseudomorphological words as primes) has led to similar facilitatory effects in semantically transparent pairs and pseudomorphological pairs (Lázaro et al 2021), supporting the results found in other languages (Beyersmann et al, 2016; Grainger & Beyersmann, 2020; Hasenäcker et al, 2016; Rastle et al, 2004). There is also evidence in Spanish showing that when derivational morphemes are used as masked primes, they facilitate the recognition of semantically transparent and pseudomorphological target words, compared to form-related controls (Lázaro, Illera, & Sainz, 2016).…”
Section: Methodssupporting
confidence: 75%
“…This study sets out to replicate and extend the findings obtained by Grainger et al (2020) employing the same manipulation with Spanish stimuli. In line with sequential processing claims, the masked priming lexical decision task in Spanish has shown that semantically transparent and pseudomorphological stimuli generate similar facilitative effects, greater than form-related control stimuli (Lázaro et al, 2021). By using the flanker task with the same stimuli however, and according to parallel processing claims, the facilitative effect for semantically transparent morphological words would be larger than for pseudomorphological words.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The results show the same facilitatory effect for the transparent as for the opaque words with no benefit for the form condition. This result has been interpreted as morphological processing taking place early in the process without any influence of the semantic relationship between primes and targets (e.g., Gold & Rastle, 2007; Lázaro, García, & Illera, 2021; Smolka, Libben, & Dressler, 2019), although this pattern of results has some exceptions (see, e.g., Feldman, O’Connor, & Moscoso del Prado Martín, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, while the influence of many factors such as prime and target word frequency, neighbourhood density, or shared neighbourhood is well known (Grainger, 2018;Mathey, 2001), no published study has reported any variation in orthographic neighbourhood priming effects with session in monolinguals (i.e., L1-to-L1 priming). In addition, masked priming studies involving other sources of linguistic activation that nonetheless lead to facilitation priming effects have yielded similar patterns of effects whether the target is presented once or multiple times (e.g., identity priming effect, see Perea et al, 2014 and for a similar approach) and a lack of interaction between priming effects and session (e.g., morphological priming effect, see Lázaro et al, 2021; Experiment 2; note, however, that sessions were conducted on two separate days).…”
Section: Discussionmentioning
confidence: 99%